Pengaruh Modifikasi Permainan Engklek Terhadap Kemampuan Motorik Kasar Dengan TEST TGMD-2 - Farida, Dwi Nur; Pratama, Indra Gunawan (CV. ITTC INDONESIA, 2024)
Motor skills are divided into 2, namely fine motor skills and gross motor skills. This research measures motor ability tests in the form of the Test of gross motor development-second edition (TGMD-2). In this experimental research there is a pretest and posttest in the form of Test of gross motor development-second edition (TGMD-2) which includes two objects, namely a locomotor object and a control object (manipulative) using treatment using modified learning through the traditional engklek game.The type of research used is experimental research. By using a True-Experimental research design. And data analysis uses the normality test, homogeneity test, and t- test after carrying out the pretest and post test. Next, the research results were analyzed using SPSS version 26.0.